GPS TECHNOLOGY FOR MONITORING SUBSIDENCE IN MERR II-C SURABAYA BRIDGE - Hariyanto, Teguh; Frandik, Achmad (Geoid, 2015)
MERR II-C bridge or road Middle East Ring Road II-C (MERR II-C) constructed as a support function sizeable transportation and vital to life, especially the area of Surabaya. Based on the results of soil testing in the area around the bridge (source: soil testing data on Soil and Rock Mechanics Laboratory, Department of Civil Engineering, FTSP - ITS, Surabaya), the type of soil surrounding is soft clay. In the soft clay soil, the problem will be found when the need to construct buildings on it are low soil bearing capacity and congestion relatively high ground (Wirawan, 2011).In this study will be an analysis of land subsidence in the area around the bridge MERR II-C, using a GPS to get a reduction in the value of the land around the bridge. Point - the point being observed there are 12 control points scattered in the area around the bridge. Observations were made 3 time is in September, October and November 2015.Output of observations obtained when the point value of land is the biggest decline 23 mm at point 8 and the largest land rise is 4 mm at point 4.